Editors’ Introduction - Bratož, Silva; Lipavic Oštir, Alja (Revija za elementarno izobraževanje, 2024)
It has been 30 years since the publication of the monograph Der monolinguale Habitus der multilingualen Schule (The Monolingual Habitus of the Multilingual School) by the German pedagogue Ingrid Gogolin, in which she uses concrete case studies to illustrate the professional attitudes and behaviour of teachers from the 19th century to the present day. Her central thesis is that in the 19th century, the German school system, as it was built within the nation state, developed a monolingual self-image. This self-image is still used as a guiding principle in schools today and as a result, migrants are at least partially excluded from the education system. Gogolin advocates a shift from crisis pedagogy to language education and inclusion as a basic component of migration research and the implementation of social and educational policy.The situation in the German school system is easily transferable to other nation states in Europe, as it is based on the unspoken assumption that classes represent linguistically homogeneous groups. The question is what kind of development has been made and in what direction in the 30 years since the criticism of the monolingual habitus of our schools was voiced? To what extent do we now actually take into account the different linguistic experiences and living conditions of pupils? And this does not just apply to the context of indigenous minority systems, but to all the contexts in which different migratory flows reach the school classroom. More broadly, this also includes the intrinsic multilingualism of pupils who are proficient in different linguistic varieties of one language. Is the professional habitus of today's teachers still monolingual in the sense that establishing monolingualism in the official national language is an imperative of the teacher's professional orientation? How do teachers today overcome the challenges of foreign language learning and acquisition in the context of indigenous and new minorities, which of course, with a few exceptions, is shared by all those involved in the school system. These are some of the questions we seek to answer in this special issue of the journal. Inclusion is today seen as an integral component of developing the competence to function successfully in a multilingual society. It requires the creation of a variety of conditions that include social and educational as well as linguistic factors. From a societal point of view, it is primarily a matter of acceptance and recognition of diversity and positive attitudes towards other languages and cultures, while in the field of education the goal is to develop programmes and guidelines that promote the successful learning (and acquisition) of foreign languages in the case of both indigenous and new minorities, highlighting the advantages of knowing several languages. The papers presented discuss these issues by asking different research questions, targeting different age groups and using a range of methodological approaches, while focusing on different school systems in Europe and beyond. Thus, by exploring the international and intercultural dimension, they reinforce the international character of the journal. Let us take a brief look at all the contributions as they appear in the journal.In the first paper, Multilingual Educational Practices at pre-primary level in Slovenia, Austria, Italy and Croatia: a Comparative Analysis, Mojca Žefran, Natascha J. Taslimi, Silvia Toniolo and Lorena Lazarić present the findings of a review study of academic articles, projects, networks and legal documents on multilingual practices at pre-primary level in Slovenia, Croatia, Austria and Italy, with the aim of assessing the current situation in the field. The results offer valuable insights and highlight the need to strengthen teachers' competences for teaching in linguistically diverse environments. The papers that follow are specific to individual school systems and environments but offer a number of transferable findings and opportunities for comparisons. Georg Traska's paper Multilingual Memory of Migration: A Participatory Oral History Project in Austria' uses the method of a participatory oral history project, involving students with their own migration and multilingual backgrounds to conduct biographical interviews, against the political backdrop of Austria's unrecognised migration history and the political paradigm of monolingualism. In this way, he contributes to the so-called national migration archive, which is not yet institutionalised in Austria. In their article Taking into account first and second language learning from the perspective of a holistic approach to the integration of migrant children in Slovenian kindergartens and schools, Sonja Rutar and Katica Pevec Semec report the results of a survey on the language needs of migrant children and the views of practitioners.  The study shows that while kindergartens and schools recognise the language needs of migrant children, teachers need additional teaching competences to implement a holistic and vertically integrated approach to the inclusion of migrant children in kindergartens and schools.In their paper entitled Motivation for and attitudes towards foreign language learning in the context of functional multilingualism, Jernej Čelofiga and Alja Lipavic Oštir explore the dynamics of language attitudes, motivation for language learning and the development of functional multilingualism in a family context in the case of daily cross-border migrants from Slovenia to Austria. The research data highlight the complex nature of linguistic identities and preferences within migrant families, as they point to a set of parallel cultural identifications and adaptations to languages and genres. The next article, entitled Mehrsprachigkeit in der deutschen Schule: Der Einfluss der eigenen Vorurteile von Lehrkräften auf den Schulerfolg der Schüler:innen mit dem sogenannten "Migrationshintergrund”, comes from the German-speaking area, where research on the development of multilingualism in the context of migration has a rich tradition. The authors, Barbara Mertins, Joël Alipaß and Katrin Odermann explore the misidentification of multilingualism with a migrant background, which is linked to the notion of the positive role of multilingualism traditionally developed by the school system. The paper uses empirical data on language evaluation to show that the equation of multilingualism with a migrant background is not sustainable and that the construct of language evaluation has a significant impact on teachers' beliefs. This calls for a new approach to multilingualism in the school context. The section concludes with the paper Zum Verhältnis von Deutschunterricht und Erstsprachenunterricht bei migrationsgesellschaftlicher Mehrsprachigkeit, in which Rainer Hawlik discusses the conditions under which many school-age multilingual children with German as a second language and as the language of the environment are educated in the Austrian school system. From a systems theory perspective, the paper provides answers to questions about teachers' capacities to deviate from monolingual representations, which is a consequence of the internalization of the unquestioned legitimization of the institutional target language German. Related to this, the author also critically discusses the importance of the socio-economic and socio-cultural context of migrant children.The articles in the next section are focused on the Slovenian education system. In their article Developing teachers' intercultural competences through international mobility programmes, Andreja Šeškar Kastelic, Silva Bratož and Anja Pirih, present a survey of primary school teachers' attitudes towards the impact of international mobility programmes on their professional and personal development. The results show that the mobility experience has a number of positive effects on the professional and personal development of the participants and on their acquisition of intercultural competences, and that the participants describe the mobility experience as a positive experience worth repeating and recommending to colleagues. The importance of developing intercultural competences is also highlighted by Melita Lemut Bajec in her paper Fostering intercultural education at tertiary level: a case study with students of humanities, in which she examines students' attitudes towards intercultural education. The results of a case study she conducted with humanities students show that the participants have positive attitudes towards intercultural education, as it promotes understanding and respect for different cultures and the development of intercultural dialogue. In the next article entitled TiDE Model - Creating Digital Materials for Multilingual Education with Future Educators, Anita Sila and Andreja Klančar discuss multilingual education using digital technologies in pre-school education according to the TiDE (Teaching in Digital Education) model. They present the results of a qualitative study which focused on the process of designing new digital didactic materials for raising plurilingual awareness. Their findings suggest that new digital technologies can be very effective in developing engaging, effective and learner-centred resources that foster multilingual awareness among learners and open attitudes towards linguistic and cultural diversity.We conclude the special issue with two articles which report on studies conducted in Namibia and Türkiye. In Analysing First Grade Teachers' Strategies for Enhancing English Reading Proficiency in Multilingual Classroom Environments in Namibia, Annaly Magda Strauss present the results of a qualitative study which suggest that teachers do not use a structured or systematic approach to support learners' reading in multilingual classrooms, relying primarily on the translation method to develop reading skills. The results of the study also show that teachers do not differentiate reading to support learners at different reading levels, emphasizing the need for new learner-centred teaching approaches. In the last article of this special issue entitled A case of early intentional bilingualism: a close examination of context and practices, Serra Kayadibli-Oğuz and Zeynep Çamlıbel-Acar discuss so-called intentional bilingualism, analysing a case study of a girl and the parents' language strategies. They conclude that the girl's linguistic environment was mostly influenced by the individuals and situations in her life, while her emotional, social, cognitive and bilingual development followed a normal course, mainly due to the special care and effort taken to ensure consistent and extensive exposure to both languages.With the launch of this special issue of the Journal of Elementary Education, we hope to have succeeded in opening up and answering some key questions, while also pointing the way to avenues and possibilities for further research.References:Gogolin, I. (1994). Der monolinguale Habitus der multilingualen Schule. Münster: Waxmann